Food Habits of Rufous-Legged Owl in a Protected Area of South-Central Chile Affected by Mixed Wildfire - Zuñiga-Alvarez, A (Sciendo, 2023)
The diet of Rufous-legged Owl, Strix rufipes, a small raptor present in an Andean protected area, is described here. During the fall of 2017, 44 pellets were collected in the study area, being subsequently analyzed. The occurrence of small mammal prey items in pellets was compared with capture frequencies with live-trapping through Sherman traps. Regarding occurrence frequencies in the diet, arthropods were the most frequent (49.34%), followed by mammals (39.31%), birds (7.86%) and reptiles (3.37%). However, in terms of biomass, mammals had the highest biomass contribution. The observed frequency of consumed preys showed a random pattern, according to the captures of small mammals obtained with Sherman traps. The role of wildfire in the composition of prey in the observed trophic spectrum of these forest owls is also discussed. © 2023 Alfredo H. Zúñiga et al., published by Sciendo.
Keywords: biomass; disturbances; selectivity; trophic behavior; rodents